The development and evaluation of new packaging and labelling for Keropok Amplang product / Siti Rohani Ismail - Ismail, Siti Rohani (2018)
This study is about the development and evaluation of new packaging and labelling for Keropok Amplang. In Sabah, there is one popular traditional food that called Keropok Amplang. The aim of this study is conducted in order to evaluate the new proposed food labeling and packaging specifically ‘Keropok Amplang’. The data analysis was divided into two phases. The first phase shows the data of perception of customer about the existing labelling and packaging of amplang’s product. For the second phase, the data derived to analyze the agreement of the new labelling and packaging of amplang product. The data analysis of these two phases involving the mean and percentage. To be able to gather the necessary data, the researcher utilize the quantitative method. Researcher started in brain storm the idea development process by doing raw sketchers to build the new packaging and labelling. At the end of this study, hopefully, this research can help the Amplang’s industry in Malaysia to expand their marketing by upgrading their labelling and packaging. Labelling and packaging proposed by researcher contains a numerous element of graphic including visual and typography that can increase the customer buy intention.